A supportive donor nerve for long-term facial paralysis: Anatomical analysis of the posterior auricular nerve and micro-anatomical comparison with zygomatic nerve. Issue 2 (February 2022) - Kara, Murat; Bitik, Ozan; Üstün, Galip Gencay; Ülkir, Mehmet; Sargon, Mustafa Fevzi; Aksu, Ali Emre
Summary: Background: The posterior auricular nerve (PAN) is an inspiring candidate for the additional axonal source in long-term facial paralysis to improve the functional results of the cross-facial nerve (FN) graft technique. However, no studies have analyzed the PAN's axonal load and its microscopic anatomy to assess its utilization in facial reanimation. The present study aims to examine the anatomical and microscopic features of the PAN to analyze its feasibility as a donor nerve. Methods: The bilateral facial side of 14 fresh frozen adult human cadavers was examined for the study. The PAN's anatomical course was recorded, and nerve specimens from the PAN and zygomatic nerve (ZN) were obtained to compare their microscopic anatomy and axon counts using a light microscope and transmission electron microscope. Results: The PAN's average branching distance and its course length were 5.8 ± 2.69 mm and 59.2 ± 5.85, respectively. The mean number of myelinated axons was 600.28 ± 69.97 in the PAN and 728.85 ± 166.31 in the ZN. This difference between the two nerves was statistically significant ( p  = 0.002). However, considering the gender variable, the mean axon counts of PAN and ZN were statistically similar for face sides and their average. Furthermore, the ultrastructural anatomy of both nerves was similar in electron microscopic evaluation. Conclusions: The present study confirms that the PAN is a proper candidate to be a supportive donor nerve due to its isolated site, consistent anatomical course, convenient ultrastructural anatomy as well as axonal load.